Altering poverty dynamics with index insurance: northern Kenya’s HSNP+ - Barrett, Christopher B.; Carter, M.R.; Chantarat, S.; McPeak, J.G.; Mude, Andrew G. (University of Wisconsin, 2008)
Abstract not available.